Factibility of using liquid and paste rations in hog feeding, during the fattening and terminal stage. - Trigueros, Rafael O. (2016)
It was the objective of this study to evaluate the efficiency of using liquid and paste food rations during the feeding of hogs, specifically the water-concentrate proportions in order to provide a significant weight gain and a larger food conversion. We utilized 40 inbred pigs of the Landrace, Yorkshire and Duroc breeds, in an experimente that lasted 60 days, with a number of treatments of 4, with 10 repetitions for each one, where we evaluated the water-concentrate ratios of 0:1,5 1:1 and 2:1. The result which were obtained showed that the value of food was improved when it was administered in a moistened form. The weight gain was presented as a significant response (P<0.001) during the treatment Nbr. 3, that is a water-concentrate ratio of 1:1. We did not observe any significant differences (P<0.001) in the remaining treatments. Data obtained showed a similar behavior in relation to the daily gain. The food conversion showed best results with treatments 2 and 3, which did not show differences between them. The results obtained in the experiment indicated that the food value of concentrates improves when supplied in a moistened form.